Dermoscopy of Rippled Pattern Sebaceoma - Mizuho Nomura; Masaru Tanaka; Maki Nunomura; Miki Izumi; Fuyuki Oryu (Dermatology Research and Practice)
A 77-year-old Japanese woman presented a dome-shaped pinkish nodule on the scalp. Dermoscopy demonstrated yellowish homogeneous ovoid areas with translucent whitish veil and arborizing vessels. No association with Muir-Torre syndrome was found. Histopathology revealed a smooth-bordered neoplasm in the dermis with partial connection to the epidermis. The tumor was composed mainly of germinative cells. The tumor focally showed a typical “rippled pattern”. There were only a few vacuolated cells suggesting sebaceous differentiation. These cells were highlighted with adipophilin antibody. No nuclear atypia or mitotic figures were observed. We regarded the neoplasm as sebaceoma. Dermoscopy demonstrated clearly visualized yellowish homogeneous ovoid areas. This feature usually corresponds to dermal conglomerations of the cells with sebaceous differentiation. However, this case histopathologically showed only limited area with sebaceous differentiation. We presented a case of rippled-pattern sebaceoma and described its dermoscopic features. This was the first report referring to the dermoscopic features of sebaceoma.